(untitled) (Global Journal of Science Frontier Research, 2023)
Background and Objective The plant Cissus pulpunea has been used as food for several years by the Idomas and Igalas speaking areas of the middle belt region Southern Guinea savanna of Nigeria Little was it known that the food crop has nutraceutical properties In this study bioactive components of Cissus populnea such as vitamin amino acids proximate mineral and phytochemical were analyzed using standard procedures Materials and Methods The stems of C pulpunea where sectioned and sent to the laboratory where Protocols for carbohydrates crude fibre crude protein Crude Fat mineral composition and oxalate were all determined Means of the replicates were obtained and recorded Results The percentage vitamins showed that Ascorbic acid had the highest value and the least was tocopherols The essential and non-essential amino acid range from 0 10- 14 48 for essential and 0 05-5 44 for non-essential in that order The percentage total amino acid of C populnea is 45 38 The proximate composition of C populnea are protein ash crude fibre fat nitrogen moisture content and carbohydrate The phytochemical results revealed the presence of some secondary metabolites found in C populnea to include flavonoids phenolics alkaloid oxalate glucosides phytate saponin trypsin inhibitors and HCN The mineral composition showed the presence of minerals as calcium magnesium potassium phosphorus sodium manganese iron zinc and copper Conclusion The study therefore supports the cultivation of C populnea with the aim of improving the bioactive components directly providing medicinal and nutritional requirements of humans